2019
DOI: 10.3389/fmars.2019.00538
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Sensitivity? Suitable Habitat for Benthic Taxa Is Surprisingly Robust to Climate Change

Abstract: Arctic marine ecosystems are often assumed to be highly vulnerable to ongoing climate change, and are expected to undergo significant shifts in structure and function. Community shifts in benthic fauna are likely to result from changes in key physicochemical drivers, such as ocean warming, but there is little ecological data on most Arctic species to support any specific predictions as to how vulnerable they are, or how future communities may be structured. We used a species distribution modeling approach (Max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 57 publications
1
39
0
Order By: Relevance
“…Arctic marine communities are at particular risk of experiencing competitive disadvantages relative to invading boreal species. Although Arctic taxa typically occupy a narrow temperature range, modeling studies suggest these taxa may be resilient to environmental pressures, including high temperatures (Renaud et al 2015(Renaud et al , 2019. Therefore, there is a need to better understand the resilience of these Arctic shelf communities to ongoing changes in the environment.…”
mentioning
confidence: 99%
“…Arctic marine communities are at particular risk of experiencing competitive disadvantages relative to invading boreal species. Although Arctic taxa typically occupy a narrow temperature range, modeling studies suggest these taxa may be resilient to environmental pressures, including high temperatures (Renaud et al 2015(Renaud et al , 2019. Therefore, there is a need to better understand the resilience of these Arctic shelf communities to ongoing changes in the environment.…”
mentioning
confidence: 99%
“…However, this particular aspect was somewhat offset by the fact that environmental conditions for reproduction, together with conditions needed for different life stages, were considered in this study during the species selection using provide valuable information to help manage resources in marine ecosystems that will face increasing anthropogenic pressures (Reiss et al, 2014) and has been shown to be a useful predictive tool to assess various taxa concurrently (Gallardo et al, 2015;Leidenberger, Obst, et al, 2015). SDM may also be particularly useful for regions such as the Arctic, where predicting biodiversity changes under global warming effects is challenging due to the paucity of baseline data for most organisms (Renaud et al, 2019;Wassmann, Duarte, Agusti, & Sejr, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The Barents Sea appears to be in transition from a cold Arctic to warm Atlantic climate regime (Lind, Ingvaldsen, & Furevik, 2018), making it particularly vulnerable to invasion. Indeed, it is predicted to suffer one of the largest future habitat losses by endemic species in the Arctic (Renaud et al., 2019), leaving potential niches available for novel species to occupy. Additionally, Arctic ecoregions will be more exposed to potential future arrivals with further ice reduction and increased navigability of the Northern Sea Route and the Northwest Passage, although much greater investment in infrastructure, navigation and communications would be needed to this end (Buixadé Farré et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate refugia could provide comparatively stable environments wherein macroalgae could persist (Ban et al, 2016;Rilov et al, 2019), and these may be identified by species distribution models (SDMs) run under climate extremes, such as the Last Glacial Maximum (LGM, 20 Kya) and the warmer Mid-Holocene (MH, 6 Kya). SDMs are powerful tools for predicting the suitable distribution area of species and to understand how they may respond to climate change (see Renaud et al, 2019). Studies applying marine-based SDMs were predominantly carried out in the temperate North Atlantic (45%) followed by studies done at the global scale (11%) and those focused on temperate Australasia (10%) (reviewed in Robinson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%